Mapping the landscape of autoimmunity and autoinflammation in inborn errors of immunity: broad distribution with distinct clustering patterns - Tahiat, Azzeddine; Touri, Souad; Saad-Djaballah, Amina; Hakem, Saliha; Fernini, Faiza; Aggoune, Samira; Belhadj, Hayet; Bendahmane, Chafa; Mokrane, Linda; Bencharif Madani, Tahar; Benhacine, Zouleikha; Melzi, Souhila; et al. (Frontiers in Immunology, 2025)
ObjectiveIn this study, we analyzed a large cohort of Algerian patients with inborn errors of immunity (IEI) to delineate the burden, spectrum, and distribution of autoimmune and autoinflammatory manifestations.MethodsThis retrospective cohort study was based on recorded data from 825 Algerian patients with IEI. For each patient, autoimmune and autoinflammatory complications occurring before and/or after IEI diagnosis were systematically assessed and documented.ResultsAutoimmune and/or autoinflammatory manifestations were observed in 217 patients (26.3%) and, notably, represented the initial clinical presentation in nearly half. Autoimmune features were documented in 163 patients (19.8%), including 26 (3.2%) with concurrent autoinflammatory findings, whereas isolated autoinflammatory conditions were observed in 54 patients (6.5%). A broad spectrum was observed, with autoimmune cytopenias predominating (11.4%), followed by gastrointestinal (7.8%), rheumatologic (5.3%), and endocrine (3.4%) disorders. Immune dysregulation was a recurrent theme across all IEI categories, with a distinct, disease-specific, clustering of autoimmunity and autoinflammation. Autoimmune cytopenias predominated in T-cell defects, including hypomorphic RAG and CD3γ deficiencies; Inflammatory bowel disease (IBD) was enriched in ARPC1B, DOCK8, and CD55 deficiencies, as well as in chronic granulomatous disease (CGD); endocrine autoimmunity, while a cardinal feature of APECED and IPEX, also characterized STAT1 gain-of-function; inflammatory granulomatous lung disease was a consistent feature in LRBA deficiency; and granulomatous inflammation, whether confined to the lungs or extending to other organs, was prominent in common variable immunodeficiency.ConclusionRecognition of clustering patterns, particularly autoimmune cytopenias, IBD, and endocrine autoimmunity, has direct clinical implications. These manifestations should be regarded as red flags, guiding targeted evaluation and genetic testing. Mapping such associations not only refines our understanding of pathogenesis but also provides a practical framework for earlier diagnosis and tailored management.